The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2002
DOI: 10.1016/s0006-3495(02)75173-4
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Concentration Fluctuations in Phase-Separated Lipid Membranes by Polypeptide Insertion

Abstract: The lateral membrane organization and phase behavior of the binary lipid mixture DMPC (1,2-dimyristoyl-sn-glycero-3-phosphatidylcholine) - DSPC (1,2-distearoyl-sn-glycero-3-phosphatidylcholine) without and with incorporated gramicidin D (GD) as a model biomembrane polypeptide was studied by small-angle neutron scattering, Fourier-transform infrared spectroscopy, and by two-photon excitation fluorescence microscopy on giant unilamellar vesicles. The small-angle neutron scattering method allows the detection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 66 publications
6
22
0
Order By: Relevance
“…Indeed, in this region we expect the two lipids to be mostly segregated into DSPC gel domains and DMPC fluid domains (40,41). From our previous results, we expect only the fluid DMPC domain fluctuations to be measurable and their amplitude to be z0.4 nm, which matches the amplitude measured in this coexistence region within the experimental error.…”
Section: Resultssupporting
confidence: 81%
“…Indeed, in this region we expect the two lipids to be mostly segregated into DSPC gel domains and DMPC fluid domains (40,41). From our previous results, we expect only the fluid DMPC domain fluctuations to be measurable and their amplitude to be z0.4 nm, which matches the amplitude measured in this coexistence region within the experimental error.…”
Section: Resultssupporting
confidence: 81%
“…A b 5.6 -helix consisting of twelve amino acids with a pitch of 5.1 would exhibit a length of approximately 29 while the corresponding b 6.3 -helix with a 3.3 pitch would feature a length of approximately 21 . [46][47][48][49][50] Considering these facts in addition to the CD results and previous studies, the distance indicated in the electron density difference curves by the major peaks that are located right beneath the lipid head-groups additionally suggest the existence of a membrane-spanning b 5.6 -helix. Especially because of the recently reported crystal structure where the peptides of the present motif seem to be slightly shorter than the typical b 5.6 -helical structure, maybe due to the steric effects of the side chains and by means of hydrophobic mismatch an extension of the considered species of 0.8 is highly reasonable.…”
Section: Membrane Incorporation Of B 56 -Helices and X-ray Reflectivitysupporting
confidence: 70%
“…The circular shape of the domains observed here ( Figure 5B), which contrasts with the gel-fluid type domains seen in Figure 2, is typical for minimizing the area-to-perimeter ratio for isotropic phases in equilibrium. This kind of shape is also observed in model raft mixtures 42 that are thought to consist of liquid-ordered/liquid-disordered domains. These findings can be explained by a lipid sorting mechanism and phase separation on the vesicle surface induced by the polypeptide.…”
Section: Discussionsupporting
confidence: 55%
“…11 Recently, we studied giant unilamellar vesicles (GUVs) of the pure lipid mixture using two different fluorophores (Laurdan and N-Rh-DPPE) in two-photon excitation fluorescence microscopy studies. 42 In the case of N-Rh-DPPE, the different probe partitioning between gel and fluid domains discriminates between fluid and gel-state domains. In the fluid phase of the lipid bilayer system, at T g 49°C, the images obtained with N-Rh-DPPE as fluorophor show that the fluorescent molecules are distributed homogeneously on the vesicle surface ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%